Molecular Imaging of the Efficacy of Heat Shock Protein 90 Inhibitors in Living Subjects - Chan, Carmel T.; Paulmurugan, Ramasamy; Gheysens, Olivier S.; Kim, Joungnam; Chiosis, Gabriela; Gambhir, Sanjiv Sam (Cancer research (Chicago, Ill.), 2008)
Heat shock protein 90α (Hsp90α)/p23 and Hsp90β/p23 interactions are crucial for proper folding of proteins involved in cancer and neurodegenerative diseases. Small molecule Hsp90 inhibitors block Hsp90α/p23 and Hsp90β/p23 interactions in part by preventing ATP binding to Hsp90. The importance of isoform-selective Hsp90α/p23 and Hsp90β/p23 interactions in determining the sensitivity to Hsp90 was examined using 293T human kidney cancer cells stably expressing split Renilla luciferase (RL) reporters. Interactions between Hsp90α/p23 and Hsp90β/p23 in the split RL reporters led to complementation of RL activity, which was determined by bioluminescence imaging of intact cells in cell culture and living mice using a cooled charge-coupled device camera. The three geldanamycin-based and seven purine-scaffold Hsp90 inhibitors led to different levels of inhibition of complemented RL activities (10–70%). However, there was no isoform selectivity to both classes of Hsp90 inhibitors in cell culture conditions. The most potent Hsp90 inhibitor, PU-H71, however, led to a 60% and 30% decrease in RL activity (14 hr) in 293T xenografts expressing Hsp90α/p23 and Hsp90β/p23 split reporters respectively, relative to carrier control–treated mice. Molecular imaging of isoform-specific Hsp90α/p23 and Hsp90β/p23 interactions and efficacy of different classes of Hsp90 inhibitors in living subjects have been achieved with a novel genetically encoded reporter gene strategy that should help in accelerating development of potent and isoform-selective Hsp90 inhibitors. [Cancer Res 2008;68(1):216–26]